Stimulation of the epithelial sodium channel (ENaC) by cAMP involves putative ERK phosphorylation sites in the C termini of the channel's beta- and gamma-subunit - Rinke, Ralf; Korbmacher, Christoph; Yang, Limin (Journal of Biological Chemistry, 2006)
The mechanisms involved in the regulation of the epithelial sodium channel (ENaC) via the cAMP pathway are not yet completely understood. The aim of the present study was to investigate cAMP-mediated ENaC regulation in Xenopus laevis oocytes heterologously expressing the three subunits (αβγ) of rat ENaC and to determine the ENaC regions important for mediating the stimulatory effect of cAMP. In oocytes treated for about 24 h with 1 mM 3-isobutyl-1-methylxanthine (IBMX) and 1 μM forskolin (FSK) so as to increase intracellular cAMP, the amiloride-sensitive whole cell current (ΔI Ami) was on average 10-fold larger than ΔI Ami in matched control oocytes. This effect on ΔI Ami was paralleled by an increase in ENaC surface expression caused by a reduced rate of ENaC retrieval. In addition, IBMX/FSK also enhanced ENaC open probability from about 0.2 to 0.5. The stimulatory effect of IBMX/FSK was dependent on the presence of intact PY motifs in the C termini of the channel. Mutagenesis of putative protein kinase A and CK-2 consensus motifs in the cytosolic domains of the channel did not reveal critical sites involved in mediating the stimulatory effect of IBMX/FSK. In contrast, site-directed mutagenesis of two putative ERK-consensus motifs (T613A in βENaC and T623A in γENaC) largely reduced the stimulatory effect of IBMX/FSK. Phosphorylation of these ERK sites has previously been reported to enhance the interaction of ENaC and Nedd4 (Shi, H., Asher, C., Chigaev, A., Yung, Y., Reuveny, E., Seger, R., and Garty, H. (2002) J. Biol. Chem. 277, 13539-13547). Using co-expression experiments we demonstrated that mutating the two ERK sites attenuates the inhibitory effect of Nedd4-2 on ENaC currents. We conclude that an increase in intracellular cAMP favors the dephosphorylation of the two ERK sites, which reduces channel retrieval and increases P O by modulating ENaC/Nedd4 interaction. This defines a novel regulatory pathway likely to be relevant for cAMP-induced stimulation of ENaC in vivo. © 2006 by The American Society for Biochemistry and Molecular Biology, Inc.
UnivIS-Import:2015-03-09:Pub.2006.med.IPK.LPVP.stimul

Transmembrane Serine Protease 2 and Proteolytic Activation of the Epithelial Sodium Channel in Mouse Kidney - Sure, Florian; Afonso, Sara; Essigke, Daniel; Schmidt, Paul; Kalo, M. Zaher; Nesterov, Viatcheslav; Kißler, Alicia; Bertog, Marko; Rinke, Ralf; Wittmann, Sabine; Broeker, Katharina A.E.; Gramberg, Thomas; et al. (Journal of the American Society of Nephrology, 2024)
Background The renal epithelial sodium channel (ENaC) is essential for sodium balance and blood pressure control. ENaC undergoes complex proteolytic activation by not yet clearly identified tubular proteases. Here, we examined a potential role of transmembrane serine protease 2 (TMPRSS2). Methods Murine ENaC and TMPRSS2 were (co-)expressed in Xenopus laevis oocytes. ENaC cleavage and function were studied in TMPRSS2-deficient murine cortical collecting duct (mCCDcl1) cells and TMPRSS2-knockout (Tmprss2−/−) mice. Short-circuit currents (ISC) were measured to assess ENaC-mediated transepithelial sodium transport of mCCDcl1 cells. The mCCDcl1 cell transcriptome was studied using RNA sequencing. The effect of low-sodium diet with or without high potassium were compared in Tmprss2−/− and wildtype mice using metabolic cages. ENaC-mediated whole-cell currents were recorded from microdissected tubules of Tmprss2−/− and wildtype mice. Results In oocytes, co-expression of murine TMPRSS2 and ENaC resulted in fully cleaved γ-ENaC and 2-fold stimulation of ENaC currents. High baseline expression of TMPRSS2 was detected in mCCDcl1 cells without a stimulatory effect of aldosterone on its function or transcription. TMPRSS2 knockout in mCCDcl1 cells compromised γ-ENaC cleavage and reduced baseline and aldosterone-stimulated ISC which could be rescued by chymotrypsin. A compensatory transcriptional upregulation of other proteases was not observed. Tmprss2−/− mice kept on standard diet exhibited no apparent phenotype, but renal γ-ENaC cleavage was altered. In response to a low-salt diet, particularly with high potassium intake, Tmprss2−/− mice increased plasma aldosterone significantly more than wildtype mice to achieve a similar reduction of renal sodium excretion. Importantly, the stimulatory effect of trypsin on renal tubular ENaC currents was much more pronounced in Tmprss2−/− mice than that in wildtype mice. This indicated the presence of incompletely cleaved and less active channels at the cell surface of TMPRSS2-deficient tubular epithelial cells. Conclusions TMPRSS2 contributes to proteolytic ENaC activation in mouse kidney in vivo.
CRIS-Team Scopus Importer:2024-11-08

Transmembrane serine protease 2 (TMPRSS2) is involved in proteolytic activation of the epithelial sodium channel (ENaC) in mouse cortical collecting duct (mCCDcl1) cells - Sure, Florian; Afonso, Sara; Bertog, Marko; Rinke, Ralf; Wittmann, Sabine; Gramberg, Thomas; Ilyaskin, Alexandr; Korbmacher, Christoph (ACTA PHYSIOLOGICA, 2022)
CRIS-Team WoS Importer:2022-10-07

Transmembrane serine protease 2 (TMPRSS2) proteolytically activates the epithelial sodium channel (ENaC) by cleaving the channel's gamma-subunit - Sure, Florian; Bertog, Marko; Afonso, Sara; Diakov, A.; Rinke, Ralf; Madej, M. G.; Wittmann, Sabine; Gramberg, Thomas; Korbmacher, Christoph; Ilyaskin, Alexandr (ACTA PHYSIOLOGICA, 2022)
CRIS-Team WoS Importer:2022-10-07

Transmembrane serine protease 2 (TMPRSS2) proteolytically activates the epithelial sodium channel (ENaC) by cleaving the channel's gamma-subunit - Sure, Florian; Bertog, Marko; Afonso, Sara; Diakov, Alexei; Rinke, Ralf; Madej, M. Gregor; Wittmann, Sabine; Gramberg, Thomas; Korbmacher, Christoph; Ilyaskin, Alexandr (Journal of Biological Chemistry, 2022)
The epithelial sodium channel (ENaC) is a heterotrimer consisting of alpha-, beta-, and gamma-subunits. Channel activation requires proteolytic release of inhibitory tracts from the extracellular domains of alpha-ENaC and gamma-ENaC; however, the proteases involved in the removal of the gamma-inhibitory tract remain unclear. In several epithelial tissues, ENaC is coexpressed with the transmembrane serine protease 2 (TMPRSS2). Here, we explored the effect of human TMPRSS2 on human alpha beta gamma-ENaC heterologously expressed in Xenopus laevis oocytes. We found that coexpression of TMPRSS2 stimulated ENaC-mediated whole-cell currents by approximately threefold, likely because of an increase in average channel open probability. Furthermore, TMPRSS2-dependent ENaC stimulation was not observed using a catalytically inactive TMPRSS2 mutant and was associated with fully cleaved gamma-ENaC in the intracellular and cell surface protein fractions. This stimulatory effect of TMPRSS2 on ENaC was partially preserved when inhibiting its proteolytic activity at the cell surface using aprotinin but was abolished when the gamma-inhibitory tract remained attached to its binding site following introduction of two cysteine residues (S155C-Q426C) to form a disulfide bridge. In addition, computer simulations and site-directed mutagenesis experiments indicated that TMPRSS2 can cleave gamma-ENaC at sites both proximal and distal to the gamma-inhibitory tract. This suggests a dual role of TMPRSS2 in the proteolytic release of the gamma-inhibitory tract. Finally, we demonstrated that TMPRSS2 knockdown in cultured human airway epithelial cells (H441) reduced baseline proteolytic activation of endogenously expressed ENaC. Thus, we conclude that TMPRSS2 is likely to contribute to proteolytic ENaC activation in epithelial tissues in vivo.
CRIS-Team WoS Importer:2022-06-24